Elasticidade-preço da demanda por gasolina em Fortaleza - Quaresma, Daniele Gadelha Lima (2020)
The objective of this study is to determine the price-elasticity of gasoline demand for the municipality of Fortaleza. In this study panel data with fixed effects were used for high frequency (daily) micro data of price and quantity of gasoline and alcohol for the 220 stations in the capital city of Ceará, from June 1st to August 31st of 2019. These data differ from the vast majority of works on the subject, which use aggregated data and annual, monthly or weekly frequency. The use of high frequency data allows a more accurate estimation of the sensitivity of automotive gasoline demand in the short term. On July 31, 2019, Petrobras announced a 4% increase in the price paid for gas stations at the refineries. In order to assess how this event affected market dynamics, measured by price elasticity, it was decided to estimate, in addition to the model for the full period, separate versions for before and after the cost shock. The results of the price elasticity of gasoline demand for the complete period show a value higher than that normally found in the literature |1.68| and a cross elasticity of alcohol price of 1.03. In the analysis of the results for the pre- and post-shock periods they indicate that there was a significant increase of 120% in the price elasticity of gasoline demand between the two moments. At the same time, there was a 45% reduction in cross elasticity. This indicates that consumers became much more sensitive to changes in gasoline prices when the market became less competitive.